2014
DOI: 10.1186/alzrt242
|View full text |Cite
|
Sign up to set email alerts
|

A controlled trial of Partners in Dementia Care: veteran outcomes after six and twelve months

Abstract: Introduction“Partners in Dementia Care” (PDC) tested the effectiveness of a care-coordination program integrating healthcare and community services and supporting veterans with dementia and their caregivers. Delivered via partnerships between Veterans Affairs medical centers and Alzheimer’s Association chapters, PDC targeted both patients and caregivers, distinguishing it from many non-pharmacological interventions. Hypotheses posited PDC would improve five veteran self-reported outcomes: 1) unmet need, 2) emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(96 citation statements)
references
References 25 publications
3
93
0
Order By: Relevance
“…In our study, the model-adjusted costs for veterans receiving the PDC intervention were not significantly higher than those for the veterans in the control arm, while, as we have documented elsewhere, veterans and their caregivers receiving PDC showed improvements in care outcomes. [7][8][9] Similar to the results in our study, those reported by Duru et al, 24 who examined the implementation of a social workeroriented intervention focused on problem and action plan prioritization, identified improvements in care quality but no differences in health care costs. Wray et al 25 noted an average decrease in total costs of $2,768/patient over 6 months, with a statistically significant reduction in costs for veterans in their intervention group (Telehealth Education Program [TEP]) over the intervention period and immediately following the intervention.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In our study, the model-adjusted costs for veterans receiving the PDC intervention were not significantly higher than those for the veterans in the control arm, while, as we have documented elsewhere, veterans and their caregivers receiving PDC showed improvements in care outcomes. [7][8][9] Similar to the results in our study, those reported by Duru et al, 24 who examined the implementation of a social workeroriented intervention focused on problem and action plan prioritization, identified improvements in care quality but no differences in health care costs. Wray et al 25 noted an average decrease in total costs of $2,768/patient over 6 months, with a statistically significant reduction in costs for veterans in their intervention group (Telehealth Education Program [TEP]) over the intervention period and immediately following the intervention.…”
Section: Discussionsupporting
confidence: 81%
“…27 Their findings are heartening in light of the similarity to what we have seen with PDC; however, they suggest that it may be important to track costs over longer periods than those used in our study. Long and colleagues 28 projected that the (2)(3)(4)(5)(6) 0.34*** 0.10 Priority group (7,8) Ref . savings from a successful dementia caregiver intervention could be substantial over the long term (15-year period), but that it might take several years to begin accruing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some implications can be drawn from integrated care studies, evidencebased research specifically on DCNs and their potential for improving the support of PwDs and their caregivers is still rare. To date, few DCN studies have been published, including studies of DCNs in Germany , Canada (Lemieux-Charles et al, 2005), and the USA (Bass et al, 2014;Kally, Cherry, Howland, & Villarruel, 2014). This gap in DCN research was addressed in the 'multi-centered, interdisciplinary evaluation study of DCNs in Germany (DemNet-D),' funded by the Federal Ministry of Health (BMG) of Germany.…”
Section: Introductionmentioning
confidence: 98%